Analisis Tingkat Kepuasan Konsumen Apotek Ainifarma - , Muhammad Fariz; , Slamet Santoso Sarwono. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Consumer Satisfaction is an essential factor of success in a pharmacy, especially for independent pharmacy to withstand the competition with chain pharmacy. One method to measure consumer satisfaction is patient satisfaction questionnaire (PSQ), which measure consumer satisfaction by 10 dimension. This researchâs purpose is to analyze the level of consumer satisfaction in Apotek Ainifarma using PSQ, then compare it to consumer satisfaction level of pharmacy in general. Thus, the strengths and weaknessess of Apotek Ainifarma can be identified, then it can be used as suggestions for manager in managing the pharmacy. The result of this research is that the level of consumer satisfaction in Apotek Ainifarma is significantly greater than pharmacy in general in 4 dimension, wich is explanation, consideration, technical competence, and efficacy of medications. It is also found that the level of consumer satisfaction in Apotek Ainifarma is rather low in 3 dimension, which is consideration, financial aspects, and continuity with the pharmacy. Management implications that occur by that result is to improve the service quality of those 3 dimension. Improvement in consideration can be done by undertake some training for employees. Improvement in financial aspects can be done by evaluate the pricing policy. Improvement in continuity with the pharmacy can be done by increasing the emotional relationship with the consumer.